Women’s experience and conception about the climate: A bibliographic review (Research, Society and Development, 2021)
Introduction: Climacteric is a period in which the transition from the reproductive to the non-reproductive period takes place, and can occur between 40 and 65 years. Objective: To know the conception of women regarding the climacteric period and the possible consequences on sexual and emotional life, through a literature review. Methodology: For the development of this research, a bibliographic review was performed, where techniques of data collection through the authors' thoughts and ideas were used. Results and Discussion: Dose (11) scientific articles, seven (07) bibliographic review. Changes during the climacteric cycle cause a confrontation during this cycle beyond the hormonal factors, interfering in the emotional, social and sexual. Conclusion: It has been shown that each woman experiences the climacteric in a unique way, as much as the age at which it starts, and the way it settles down, being natural or surgical.